2022
DOI: 10.1101/2022.11.11.516176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PRRC2 proteins regulate translation initiation by promoting leaky scanning

Abstract: Roughly half of animal mRNAs contain upstream Open Reading Frames (uORFs). These uORFs represent an impediment to translation of the main ORF since ribosomes usually bind the mRNA cap at the 5' end and then scan for ORFs in a 5'-to-3' fashion. One way for ribosomes to bypass uORFs is via leaky scanning, whereby the ribosome disregards the uORF start codon. Hence leaky scanning is an important instance of post-transcriptional regulation that affects gene expression. Few molecular factors regulating or facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…These secondary or compensatory effects could result from the primary changes in TE of PRRC2B-bound mRNAs or the altered cell cycle progression upon PRRC2B knockdown (Figure 4) since translation varies dramatically in different phases of cell cycle (46). The PRRC2 proteins have been repeatedly linked with mRNA binding and posttranscriptional regulation (21)(22)(23)(47)(48)(49)(50). A recent study suggests that PRRC2 proteins facilitate leaky scanning of upstream open reading frames (uORF) (47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These secondary or compensatory effects could result from the primary changes in TE of PRRC2B-bound mRNAs or the altered cell cycle progression upon PRRC2B knockdown (Figure 4) since translation varies dramatically in different phases of cell cycle (46). The PRRC2 proteins have been repeatedly linked with mRNA binding and posttranscriptional regulation (21)(22)(23)(47)(48)(49)(50). A recent study suggests that PRRC2 proteins facilitate leaky scanning of upstream open reading frames (uORF) (47).…”
Section: Discussionmentioning
confidence: 99%
“…The PRRC2 proteins have been repeatedly linked with mRNA binding and posttranscriptional regulation (2123,4750). A recent study suggests that PRRC2 proteins facilitate leaky scanning of upstream open reading frames (uORF) (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent preprint showed that the eIF4G2-interacting proteins PRRC2A, PRRC2B, and PRRC2C also promote leaky scanning on certain, but not all, mRNAs ( Bohlen et al 2022 ). Strikingly, subsets of mRNAs that require eIF4G2 or PRRC2A-C for their translation at least partially overlap ( Bohlen et al 2022 ; Smirnova et al 2022 ). Future research will show how these proteins cooperate in facilitating leaky scanning.…”
Section: Proposed Mechanisms Of Eif4g2 Operation In Translation Initi...mentioning
confidence: 99%